Prenatal exposure to glycol ethers and cryptorchidism and hypospadias: a nested case–control study. Issue 1 (21st October 2017) - Warembourg, Charline; Botton, Jérémie; Lelong, Nathalie; Rouget, Florence; Khoshnood, Babak; Le Gléau, Florent; Monfort, Christine; Labat, Laurence; Pierre, Fabrice; Heude, Barbara; Slama, Rémy; Multigner, Luc; et al.
Abstract : Objectives: Glycol ethers (GE) are oxygenated solvents frequently found in occupational and consumer products. Some of them are well-known testicular and developmental animal toxicants. This study aims to evaluate the risk of male genital anomalies in association with prenatal exposure to GE using urinary biomarkers of exposure. Methods: We conducted a case–control study nested in two joint mother–child cohorts (5303 pregnant women). Cases of cryptorchidism and hypospadias were identified at birth and confirmed during a 2-year follow-up period (n=14 cryptorchidism and n=15 hypospadias). Each case was matched to three randomly selected controls within the cohorts for region of inclusion and gestational age at urine sampling. Concentrations of five GE acidic metabolites were measured in spot maternal urine samples collected during pregnancy. ORs were estimated with multivariate conditional logistic regressions including a Firth's penalisation. Results: Detection rates of urinary GE metabolites ranged from 8% to 93% and only two were sufficiently detected (>33%) in each cohort to be studied: methoxyacetic acid (MAA) and phenoxyacetic acid (PhAA). A significantly higher risk of hypospadias was associated with the highest tertile of exposure to MAA: OR (95% CI) 4.5(1.4 to 23.4). No association were observed with urinary concentration of PhAA, nor with the risk of cryptorchidism. Conclusions: In view of the toxicological plausibility of our results, this study, despite its small sample size, raises concern about the potential developmental toxicity of MAA on the male genital system and calls for thorough identification of current sources of exposure to MAA.